Chemical composition of Ocimum sanctum by GC-MS Analysis (Al-Mukhtar Journal of Basic Sciences, 2026)
The chemical composition of the n-hexane extract from the aerial parts of Ocimum sanctum., was investigated using gas chromatography-mass spectrometry (GC/MS), identifying 46 different compounds. Terpenoids were the most abundant, with monoterpenes representing 21.82% of the extract. The primary components identified were methyl eugenol (27.24%), squalene (11.84%) α-bergamotene (9.83%), linalool (8.42%), and fenchyl acetate (7.56%). These results indicate that O. sanctum could serve as a valuable source of food and medicinal agents.